Antecedents and Consequences of Organizational Citizenship Behavior in the Covid-19 Pandemic Era - Nadia Iftinan Alfiana; Siswoyo Haryono; Nuryakin Nuryakin (Profesional Muda Cendekia Publishing, 2022)
Organizational conditions after the COVID-19 pandemic forced almost all countries to take steps to reduce employees and cut employee salaries. Organizations must cultivate employee commitment to improving HR performance so that organizations can compete in this era. In this way, it can also effectively make organizational members feel uncomfortable due to the many changes that occur to survive and not leave the organization. Organizational citizenship behavior of employees is an important part that is also considered in the effectiveness of this philanthropic activity. Employees who avoid pettiness, do not complain about trivial things, and have manners to prevent work-related problems with other employees will create a healthy working atmosphere. This study aimed to examine the effect of workplace spirituality, Islamic work ethics, and organizational citizenship behavior on employee commitment in the Covid-19 Pandemic Era. This study uses two exogenous variables, namely workplace spirituality and Islamic work ethics, and endogenous variables, namely employee commitment and organizational citizenship behavior, as intervening variables. Data were collected from 61 respondents at philanthropic institutions of the Special Region of Yogyakarta. The sampling technique in this study used a non-probability sampling method, namely the saturated sample. The data analysis technique in this study uses Structural Equation Modeling with the help of SmartPLS 3. The results of this study indicate that all proposed hypotheses have been accepted. The mediating role of organizational citizenship behavior for X1 and X2 is partial mediation, or mediation does not play a full role. So the presence or absence of organizational citizenship behavior, these two variables still affect employee commitment.